Influence of Buddhism in the cultural life of Vietnamese people - Duc, Tran Minh (Technium Social Sciences Journal, 2022)
After over 2000 years of spreading into Vietnam, Buddhism has naturally entered the lives of Vietnamese people and established a firm foothold from urban to rural areas throughout the country. Buddhist ethics have also become vital spiritual ideals for the Vietnamese people, having become profoundly engrained in their way of life and thinking. Throughout its approximately two-hundred-year history, Buddhism has demonstrated its presence in almost every sphere of politics, economy, culture, society, and so on, and has had a good influence on all of these elements in Vietnam.